(untitled) (Jurnal Wahana Konseling, 2026)
Self-awareness is an important psychological capacity for junior high school students because it helps them recognize emotions, evaluate personal strengths and weaknesses, and develop confidence in academic and social interactions. This study aimed to examine the effect of classical guidance services using mindfulness techniques on improving students’ self-awareness at SMP Al-Azhar 37 Pekanbaru. The study used a quantitative experimental approach with a one-group pretest-posttest design. The participants were 21 seventh-grade students selected through purposive sampling based on low self-awareness scores. Data were collected using a self-awareness scale developed from Goleman’s three aspects: emotional self-awareness, accurate self-assessment, and self-confidence. The instrument consisted of 35 valid items with a Cronbach’s alpha coefficient of 0.944. The intervention was conducted in six treatment sessions using breathing meditation, body scan meditation, sitting meditation, and walking meditation. Data were analyzed using descriptive statistics, the Wilcoxon Signed-Rank Test, and normalized gain. The results showed that students’ self-awareness increased from mostly low and moderate categories to mostly high categories after the intervention. The highest improvement occurred in self-confidence. The Wilcoxon test showed a significant difference between pretest and posttest scores (p < .05), while the N-Gain score of 0.76 indicated a high level of overall improvement among students